2013
DOI: 10.1063/1.4811976
|View full text |Cite
|
Sign up to set email alerts
|

Study of some micro-structural phenomena in granular shear zones

Abstract: Abstract. The paper deals with some characteristic phenomena of fundamental nature which occur within shear zones in granular materials. Phenomena such as self-organizing force chain networks, vortices, alternating contractant and dilatant regions within shear zones were modelled numerically using discrete element method DEM. Discrete simulations were carried out with medium-dense sand during direct a shearing test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Previous studies investigated the influence of the contact rolling resistance properties on the macroscopic behavior [23,36,35,18]. All the results showed that increasing the rolling elastic stiffness causes an increase in the macroscopic internal friction angle, but has little influence on the dilatancy [23,36].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated the influence of the contact rolling resistance properties on the macroscopic behavior [23,36,35,18]. All the results showed that increasing the rolling elastic stiffness causes an increase in the macroscopic internal friction angle, but has little influence on the dilatancy [23,36].…”
Section: Introductionmentioning
confidence: 99%